Analisis Pending Klaim BPJS Kesehatan Pasien Rawat Inap Di Rumah Sakit Islam Jakarta Pondok Kopi Tahun 2023 - Sri Mulya; Dina Sonia; Daniel Happy Putra; Noor Yulia (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Pending BPJS Health claims at RSIJ Pondok Kopi are divided into 3 (three) aspects including administration, coding and medical. This research aims to determine the factors of causes pending claims, resolution, and pending trends using a descriptive quantitative approach, which provides an overview of the factors causing pending claims and pending trends in 2023. Results with 1,143 samples of pending claim reports due to administration 523 (46%) with the most pending categories due to inappropriate treatment class 120 (23%), causative factors due to coding 570 (50%) with the most pending categories due to inaccurate diagnosis 525 (92.1%), and factors medical causes 50 (4%) with the most pending category due to inappropriate medical indications 36 (72%). So the pending settlement is carried out after receiving the verification results report by the casemix officer by completing the claim requirements according to the pending claim category and confirming with the DPJP if necessary. The pending trend in 2023 for 1st semester period January to June showed decreasing results with a significant decrease in March of 12%. To minimize pending figures, hospitals should recruit employees according to their field of competence, empower existing human resources by clinical coding training, implement RME so that RM documentation is more complete, and internal verification officers are more thorough in carrying out their work.